Ochratoxin A-Induced Nephrotoxicity: Up-to-Date Evidence - Khoi, Chong-Sun; Chen, Jia-Huang; Lin, Tzu-Yu; Chiang, Chih-Kang; Hung, Kuan-Yu (International journal of molecular sciences, 2021)
Ochratoxin A (OTA) is a mycotoxin widely found in various foods and feeds that have a deleterious effect on humans and animals. It has been shown that OTA causes multiorgan toxicity, and the kidney is the main target of OTA among them. This present article aims to review recent and latest intracellular molecular interactions and signaling pathways of OTA-induced nephrotoxicity. Pyroptosis, lipotoxicity, organic anionic membrane transporter, autophagy, the ubiquitin-proteasome system, and histone acetyltransferase have been involved in the renal toxicity caused by OTA. Meanwhile, the literature reviewed the alternative or method against OTA toxicity by reducing ROS production, oxidative stress, activating the Nrf2 pathway, through using nanoparticles, a natural flavonoid, and metal supplement. The present review discloses the molecular mechanism of OTA-induced nephrotoxicity, providing opinions and strategies against OTA toxicity.